2020
DOI: 10.3389/fmicb.2020.00438
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mutations Against Protease, Reverse Transcriptase and Integrase Inhibitors in People Living With HIV-1 Receiving Boosted Protease Inhibitors in South Africa

Abstract: The South African national combination antiretroviral therapy (cART) roll-out program started in 2006, with over 4.4 million people accessing treatment since it was first introduced. HIV-1 drug resistance can hamper the success of cART. This study determined the patterns of HIV-1 drug-resistance associated mutations (RAMs) in People Living with HIV-1 (PLHIV-1). Receiving first (for children below 3 years of age) and second-line (for adults) cART regimens in South Africa. During 2017 and 2018, 110 patients plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 36 publications
4
23
0
Order By: Relevance
“…Even though there is no indication of the patients being administered RAL, three of the patients in our study harbored Y143R mutation in > 20% of the population. Previous studies on HIV-1C have shown major INI mutations at baseline in less than 5% of patients from Ethiopia (T66I, E138K, Q148R, and Q148H) and South Africa (Q148H, T66S, E92G, S147G, T66A, Y143YF and Y143H) [3,5,14]. However, the presence of INI RAMs in minor viral population is deemed not to have any clinical consequences [28].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though there is no indication of the patients being administered RAL, three of the patients in our study harbored Y143R mutation in > 20% of the population. Previous studies on HIV-1C have shown major INI mutations at baseline in less than 5% of patients from Ethiopia (T66I, E138K, Q148R, and Q148H) and South Africa (Q148H, T66S, E92G, S147G, T66A, Y143YF and Y143H) [3,5,14]. However, the presence of INI RAMs in minor viral population is deemed not to have any clinical consequences [28].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma samples were obtained from bPIs suspected of failing patients (as referred by the clinician) from the diagnostic section at the Division of Medical Virology, Stellenbosch University, and the South African National Health Laboratory Services (NHLS), and were collected between March 2017 and February 2018 [5,18]. We excluded patient samples with no previous cART regimen history and patients receiving rstline cART treatment regimens.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that diverse subtypes may affect the clinical treatment outcome in patient management (1). In Cameroon, HIV-1 CRF02_AG continues to be the predominant subtype causing infection, with most other strains, including groups N, O and P, circulating in the country and accounting for a smaller proportion of infections (2,3). Previous studies have shown that different HIV subtypes may support different mutational pathways, and this could lead to subtype-based differences in acquiring drug resistance (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%